Partisan Fertility and Presidential Elections - Gordon B. Dahl; Runjing Lu; William Mullins (Institute of Labor Economics (IZA), 2021)
Changes in political leadership drive sharp changes in public policy and partisan beliefs about the future. We exploit the surprise 2016 election of Trump to identify the effects of a shift in political power on one of the most consequential household decisions: whether to have a child. Republican-leaning counties experience a sharp and persistent increase in fertility relative to Democratic counties, a shift amounting to 1.2 to 2.2% of the national fertility rate. In addition, Hispanics see fertility fall relative to non-Hispanics, especially compared to rural or evangelical whites.
Keywords: J13; D72; 330; fertility; partisanship; elections